Biochar-loaded nano zero-valent iron composite material as well as preparation method and application thereof

The preparation of biochar-loaded nano zero-valent iron composite material through co-pyrolysis method of biomass and nano zero-valent iron is solved, and the problems of low tetracycline removal rate and complex preparation in the prior art are achieved, and efficient and low-cost wastewater treatment is achieved. And it exhibits excellent removal effect within a wide pH range.

CN119236879APending Publication Date: 2025-01-03HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484965.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing biochar-loaded nano zero-valent iron composites have low tetracycline removal rate in wastewater, complex preparation methods and high cost, and the biomass pyrolysis process is uncontrollable, which limits the full utilization of biomass materials.

Method used

The direct co-pyrolysis method of biomass materials and nano zero-valent iron particles is used to prepare biochar-loaded nano zero-valent iron composite materials. The pyrolysis is carried out by pulverizing biomass and nano zero-valent iron to form a stable composite material. Removal of tetracycline in wastewater.

Benefits of technology

It improves the removal rate of tetracycline, simplifies the preparation process, reduces costs, improves the utilization rate of biomass, and shows good removal effect within a wide pH range, which is in line with the concept of "use waste to control waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236879A_ABST
    Figure CN119236879A_ABST
Patent Text Reader

Abstract

The invention provides a biochar loaded nano zero-valent iron composite material as well as a preparation method and application thereof, belongs to the technical field of wastewater treatment, and aims at solving the technical problem that the removal rate of tetracycline in wastewater is low when an nZVI-BC composite material is prepared by a one-step pyrolysis method or a co-pyrolysis method. Nano zero-valent iron and a biomass material are mixed and carbonized, so that nZVI is loaded on the surface and in pores of BC, the binding capacity of nZVI and BC is improved, the preparation method comprises the following steps: crushing the biomass material, uniformly mixing the crushed biomass material with nano zero-valent iron particles to obtain a mixture, and pyrolyzing the mixture to obtain the biochar loaded nano zero-valent iron composite material. The invention discloses a method for preparing the biochar composite material in a direct embedding manner by using nano zero-valent iron for the first time, and the prepared BC-nZVI composite material has very high adsorption capacity on antibiotics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wastewater treatment, and in particular relates to a biochar-loaded nano zero-valent iron composite material and a preparation method and application thereof. Background Art

[0002] Tetracycline (TC) is a universal antibiotic widely used in human medicine, animal husbandry, animal disease prevention and control, etc. Due to the overuse / abuse of such drugs and their incomplete metabolism in organisms, TC has become a common new pollutant in wastewater and poses a potential threat to human health. Therefore, how to efficiently eliminate TC in wastewater is a problem that current wastewater treatment technology needs to solve.

[0003] At present, the main methods used to remove tetracycline antibiotics from wastewater include photocatalytic degradation, chemical oxidation, adsorption, biodegradation and membrane filtration. Among them, adsorption is widely regarded as one of the most economical and effective methods. Among the more widely used adsorbent materials, biochar (BC) is considered to be an efficient, cheap and readily available adsorbent due to its physical and chemical properties. Biochar refers to a carbon-rich substance obtained by high-temperature pyrolysis of biomass materials under oxygen-limited conditions. It has characteristics such as high specific surface area and oxygen-containing functional groups; it shows good application potential in soil remediation and sewage treatment. However, the removal effect of most biochars on antibiotics is not ideal, which brings certain challenges to the application of biochar materials in environmental remediation.

[0004] In order to improve the removal effect of biochar on pollutants in water bodies, an effective way is to modify biochar. Nano-zero-valent iron (nZVI) is a typical metal nanomaterial with high activation energy, high specific surface area and environmental friendliness. Because of its good adsorption capacity, it can be used to remove organic pollutants in water bodies. However, due to its high reactivity and micromagnetism, nZVI is easy to agglomerate in water environments, which limits the widespread use of this metal nanomaterial. Combining the characteristics of biochar and nZVI, biochar can be used as a carrier of nZVI particles to prepare a biochar-loaded nano-zero-valent iron composite material (nZVI-BC) for the removal of antibiotic pollutants in water bodies.

[0005] In the existing reported technology (Chinese patent document CN117620199A), the preparation method of nZVI-BC is usually a pyrolysis-liquid phase reduction method and a one-step pyrolysis method. Among them, the pyrolysis-liquid phase reduction method requires the preparation of biochar first, and then the iron salt-impregnated biochar is reduced by a reducing agent (such as hydrazine hydrate, hydrogen, and sodium borohydride, etc.) to prepare the nZVI-BC composite material. This method has a complicated process, the cost of the reducing agent used is high, and the reduction process will destroy the surface structure of the biochar. Relatively speaking, the co-pyrolysis method requires high-temperature pyrolysis to generate nano zero-valent iron-biochar, which has a simple preparation operation and has the potential for large-scale production and application.

[0006] There are also some patent documents reporting on the preparation of nZVI-BC composite materials by co-pyrolysis. For example, Chinese patent document CN114433020A reports a method for preparing a composite material of zero-valent iron fixed by biochar by co-pyrolysis. Hematite and biomass are added to deionized water, stirred thoroughly, and then ultrasonically treated. After drying, they are pyrolyzed in a tubular furnace (700-900°C) to obtain a composite material of zero-valent iron fixed by biochar as an adsorbent for tetracycline; however, in order to enable the biomass pyrolysis process to produce sufficient reducing gases such as CO and H2 to reduce hematite to zero-valent iron, the mass ratio of hematite to biomass used is 1:4-6. This not only results in the uncontrollable reduction effect, but also limits the full utilization of biomass materials. Summary of the invention

[0007] In order to solve the technical problem of low tetracycline removal rate in wastewater by preparing nZVI-BC composite materials by one-step pyrolysis or co-pyrolysis, the present invention proposes a biochar-loaded nano zero-valent iron composite material and a preparation method and application thereof. The preparation process is simple, the utilization rate of biomass is high, and tetracycline in wastewater can be efficiently adsorbed.

[0008] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0009] A method for preparing a biochar-loaded nanometer zero-valent iron composite material comprises the following steps: crushing a biomass material and uniformly mixing it with nanometer zero-valent iron particles to obtain a mixture, and pyrolyzing the mixture to obtain the biochar-loaded nanometer zero-valent iron composite material.

[0010] The biomass material is forestry and / or agricultural waste.

[0011] The biomass material is pine wood chips.

[0012] The mass ratio of the biomass material to the nano zero-valent iron particles is 100:(0.5-5).

[0013] The particle size of the nano zero-valent iron particles is 5-500nm.

[0014] The pyrolysis temperature is 300-900° C., the pyrolysis time is 2-5 hours, and the pyrolysis process is carried out in an oxygen-free environment.

[0015] A biochar-loaded nanometer zero-valent iron composite material, wherein the particle size of the biochar-loaded nanometer zero-valent iron composite material is not greater than 150 μm.

[0016] The invention discloses an application of a biochar-loaded nano zero-valent iron composite material in wastewater treatment, characterized in that tetracycline in wastewater is removed, and the specific steps are as follows: adding the biochar-loaded nano zero-valent iron composite material to wastewater containing TC, adjusting the pH of the wastewater and subjecting it to constant temperature treatment, and then performing solid-liquid separation to remove solid materials in the system.

[0017] The concentration of the biochar-loaded nano zero-valent iron composite material in wastewater is 0.4-1.0 g / L.

[0018] The pH value is 7-8; the temperature of the constant temperature treatment is 20-30°C.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention co-pyrolyzes forestry waste and nZVI to obtain a stable BC-nZVI composite material; and discloses for the first time a method for preparing a biochar composite material by directly embedding nano zero-valent iron; the prepared BC-nZVI composite material has a high adsorption capacity for antibiotics.

[0021] 2. The BC-nZVI composite material of the present invention uses forestry solid waste and commercial nZVI as raw materials, avoiding the problem of difficult control of nZVI morphology during pyrolysis-liquid phase reduction or one-step pyrolysis, and has a high utilization rate of biomass materials. The required raw materials are widely available and easy to obtain; it can save costs and realize the resource utilization of solid waste.

[0022] 3. The BC-nZVI composite material involved in the present invention has stable performance and shows a good removal effect on TC in water within a relatively wide pH range (3.0-10.0), which is in line with the waste resource utilization concept of "treating waste with waste".

[0023] 4. The BC-nZVI composite material of the present invention has a simple preparation process, low cost, short production cycle, and is easy to realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 Scanning electron microscope (SEM) images: (a) biochar (BC); (b) biochar loaded with nano zero-valent iron composite material (BC-nZVI).

[0026] Figure 2 Fourier transform infrared (FTIR) spectra of BC and BC-nZVI.

[0027] Figure 3 This is the X-ray photoelectron spectroscopy (XPS) diagram of BC-nZVI.

[0028] Figure 4 Effect of reaction time on the removal of TC from water by BC and BC-nZVI

[0029] Figure 5 This is the effect of initial TC concentration on the removal of TC from water by BC and BC-nZVI.

[0030] Figure 6 This is the effect of the addition amount of the same composite material on the removal of TC in water by BC-nZVI.

[0031] Figure 7 This is the effect of different solution pH on the removal of TC in water by BC-nZVI.

[0032] Figure 8 The effect of different temperatures and pH on the removal of TC from water by BC-nZVI. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A biochar-loaded nano zero-valent iron composite material, the preparation method comprising the following steps:

[0036] (1) Place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly for 5 times, and then dry the washed chips at 105°C for later use;

[0037] (2) 100 g of cleaned pine sawdust and 1.0 g of nZVI particles with a particle size of 50 nm (purchased from Yumu (Ningbo) New Materials Co., Ltd.) were weighed, mixed evenly, and pyrolyzed in a tube furnace at 750°C. N2 was introduced as a protective carrier gas throughout the pyrolysis process, and the flow rate was maintained at 0.5 L / min. The pyrolysis time was 3 h.

[0038] (3) After the sample is cooled to room temperature, the solid product is collected to obtain a BC-nZVI composite material.

[0039] (4) The BC-nZVI composite material was ground and passed through a 100-mesh sieve.

[0040] Comparative Example 1

[0041] The difference from the above-mentioned Example 1 is that in Comparative Example 1, only pine wood chip biomass is pyrolyzed alone to prepare the BC sample.

[0042] From Table 1, we can see that the specific surface area of ​​BC-nZVI composite material has been greatly improved compared with pure BC. This may be because nZVI itself has a huge specific surface area, which increases the specific surface area of ​​the composite material. Figure 1 The scanning electron microscope (SEM) image of the BC-nZVI composite material clearly shows that some nZVI particles with uniform particle size are embedded on the surface of biochar, indicating that direct co-pyrolysis of biomass and nZVI can successfully prepare a BC-loaded nZVI composite material. Figure 2 The Fourier transform infrared spectroscopy (FTIR) of the BC-nZVI composite material shows that it contains a large number of oxygen-containing functional groups on its surface, 690 cm -1 The absorption peak at is the Fe-O vibration peak, indicating that the BC-nZVI composite material was successfully prepared. Figure 3 X-ray photoelectron spectroscopy (XPS) of the BC-nZVI composite also verified that nZVI was successfully loaded onto biochar.

[0043] Table 1. Elemental analysis and specific surface area

[0044]

[0045] BC is pure biochar, and BC-nZVI is biochar loaded with zero-valent iron.

[0046] Example 2

[0047] A biochar-loaded nano zero-valent iron composite material, the preparation method comprising the following steps:

[0048] (1) Place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly for 5 times, and then dry the washed chips at 105°C for later use;

[0049] (2) 100 g of cleaned pine sawdust and 0.5 g of nZVI particles with a particle size of 10 nm were weighed, mixed evenly, and pyrolyzed in a tube furnace at 500°C. N2 was introduced as a protective carrier gas throughout the pyrolysis process, and the flow rate was maintained at 0.3 L / min. The pyrolysis time was 5 h.

[0050] (3) After the sample is cooled to room temperature, the solid product is collected to obtain a BC-nZVI composite material.

[0051] (4) The BC-nZVI composite material was ground and passed through a 100-mesh sieve.

[0052] Example 3

[0053] A biochar-loaded nano zero-valent iron composite material, the preparation method comprising the following steps:

[0054] (1) Place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly for 5 times, and then dry the washed chips at 105°C for later use;

[0055] (2) 100 g of cleaned pine sawdust and 3 g of nZVI particles with a particle size of 5 nm were weighed, mixed evenly, and pyrolyzed in a tube furnace at 300°C. N2 was introduced as a protective carrier gas throughout the pyrolysis process, and the flow rate was maintained at 0.7 L / min. The pyrolysis time was 3 h.

[0056] (3) After the sample is cooled to room temperature, the solid product is collected to obtain a BC-nZVI composite material.

[0057] (4) The BC-nZVI composite material was ground and passed through a 100-mesh sieve.

[0058] Example 4

[0059] A biochar-loaded nano zero-valent iron composite material, the preparation method comprising the following steps:

[0060] (1) Place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly for 5 times, and then dry the washed chips at 105°C for later use;

[0061] (2) 100 g of cleaned pine sawdust and 5 g of nZVI particles with a particle size of 500 nm were weighed, mixed evenly, and pyrolyzed in a tube furnace at 900°C. N2 was introduced as a protective carrier gas throughout the pyrolysis process, and the flow rate was maintained at 0.6 L / min. The pyrolysis time was 3 h.

[0062] (3) After the sample is cooled to room temperature, the solid product is collected to obtain a BC-nZVI composite material.

[0063] (4) The BC-nZVI composite material was ground and passed through a 100-mesh sieve.

[0064] Example 5

[0065] A biochar-loaded nano zero-valent iron composite material, the preparation method comprising the following steps:

[0066] (1) Place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly for 5 times, and then dry the washed chips at 105°C for later use;

[0067] (2) 100 g of cleaned pine sawdust and 3.0 g of nZVI particles with a particle size of 300 nm were weighed, mixed evenly, and pyrolyzed in a tube furnace at 500°C. N2 was introduced as a protective carrier gas throughout the pyrolysis process, and the flow rate was maintained at 0.5 L / min. The pyrolysis time was 2 h.

[0068] (3) After the sample is cooled to room temperature, the solid product is collected to obtain a BC-nZVI composite material.

[0069] (4) The BC-nZVI composite material was ground and passed through a 100-mesh sieve.

[0070] Application Example 1

[0071] This application example tests the effect of reaction time on the removal of TC from water by the materials prepared in Example 1 and Comparative Example 1.

[0072] 20 mL of 20 mg / L TC aqueous solution was used as simulated wastewater (pH 7.0, ionic strength 10 mol / L NaCl), 15 mg of BC and BC-nZVI composite materials were added respectively, and the mixture was shaken at 200 rpm in a constant temperature electric oscillator (25 ° C), and samples were taken at 0.1, 0.3, 0.5, 1, 3, 6, 9, 12, 18, 21, and 24 h. The sample was centrifuged at 8000 rpm for 30 min, the supernatant was filtered through a 0.45 μm membrane filter, and then the concentration of TC in the supernatant was analyzed. The test results are as follows Figure 4 As shown. Within 1 hour, the TC removal rates of both materials increased rapidly; after 3 hours, the growth rate began to slow down. The TC removal rate of BC-nZVI reached 67.6% within 0.5 hours. As the reaction time increased, the TC removal rate of BC-nZVI also gradually increased, reaching equilibrium after 12 hours, and the total removal rate was 99.1%. In general, under the same stable working conditions, the TC removal effect of BC-nZVI was significantly stronger than that of BC material.

[0073] Application Example 2

[0074] This application example tests the effect of initial TC concentration on the removal of TC from water by the materials prepared in Example 1 and Comparative Example 1.

[0075] 20mL of TC aqueous solution with different concentrations was used as simulated wastewater (concentrations were 1, 5, 10, 20, 30, 50 and 80mg / L, pH was 7.0, and ionic strength was 10mol / LNaCl), 15mg of BC and BC-nZVI composite materials were added respectively, and oscillated at 200rpm in a constant temperature electric oscillator (25℃), and samples were taken after equilibrium adsorption for 24h. The sample was centrifuged at 8000rpm for 30min, the supernatant was filtered through a 0.45μm membrane filter, and then the concentration of TC in the supernatant was analyzed. The test results are as follows Figure 5 As shown in the figure, the BC-nZVI composite material of the present invention has a higher TC removal rate than pure BC material in the concentration range of 1-80 mg / L. Even when the TC concentration is as high as 80 mg / L, the TC removal rate of BC-nZVI is still as high as 96.7%.

[0076] Application Example 3

[0077] This application example tests the TC effect of the material prepared in Example 1 with different addition amounts in water.

[0078] In 20mL of 20mg / L TC solution (pH 7.0, ionic strength 10mol / LNaCl), 8mg, 10mg, 15mg and 20mg of the BC-nZVI composite material prepared in Example 1 (the corresponding material concentrations were 0.4g / L, 0.5g / L, 0.75g / L and 1g / L, respectively) were added, and the mixture was shaken at 200rpm in a constant temperature electric shaker (25°C), and samples were taken after 24h of equilibrium adsorption. The sample was centrifuged at 8000rpm for 30min, the supernatant was filtered through a 0.45μm membrane filter, and then the concentration of TC in the supernatant was analyzed. The test results are as follows: Figure 6 As shown in the figure, as the addition amount of BC-nZVI composite material increases from 8mg to 15mg, the removal rate of TC increases from 93.5% to 99.3%; further increasing the addition amount does not significantly improve the removal effect. Therefore, for treating TC solutions with a concentration of less than 20mg / L, the use concentration of BC-nZVI composite material should not be higher than 0.75g / L.

[0079] Application Example 4

[0080] This application example tests the effect of different solution pH on the material prepared in Example 1 in removing TC from water.

[0081] 20 mL of 20 mg / L TC aqueous solution with different pH values ​​was used as simulated wastewater (pH values ​​were 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0 and 10.0, and the ionic strength was 10 mol / L NaCl), 15 mg of the BC-nZVI composite material prepared in Example 1 (the concentration of the corresponding material was 0.75 g / L) was added respectively, and the mixture was oscillated at 200 rpm in a constant temperature electric oscillator (25°C), and samples were taken after 24 hours of equilibrium adsorption. The sample was centrifuged at 8000 rpm for 30 min, the supernatant was filtered through a 0.45 μm membrane filter, and then the concentration of TC in the supernatant was analyzed. The test results are as follows: Figure 7 The BC-nZVI composite material of the present invention has a high removal rate (>90%) for TC within the pH range of 3.0-10.0, and the optimal pH application range is 7.0-8.0.

[0082] Application Example 5

[0083] This application example tests the effect of the material prepared in Example 1 on removing TC from water at different temperatures.

[0084] 20 mL of 20 mg / LTC aqueous solution was used as simulated wastewater (pH 7.0, ionic strength 10 mol / L NaCl), 15 mg of BC-nZVI composite material prepared in Example 1 (the corresponding material concentration was 0.75 g / L) was added, and the mixture was shaken at 200 rpm in a constant temperature electric oscillator. The reaction temperatures were 25°C, 35°C and 45°C respectively; samples were taken after 24 hours of equilibrium adsorption. The sample was centrifuged at 8000 rpm for 30 minutes, the supernatant was filtered through a 0.45 μm membrane filter, and then the concentration of TC in the supernatant was analyzed. The test results are as follows: Figure 8 As shown in the figure, the removal rate of TC by the BC-nZVI composite material of the present invention increases with decreasing temperature. Therefore, considering the actual conditions, the optimal application temperature should be 25°C.

[0085] In Example 1, direct pyrolysis of biomass and nZVI was used, and the yield of biochar obtained after pyrolysis of biomass was about 34.1%. Therefore, it was calculated that the ratio of BC to nZVI in the material finally obtained in Example 1 (the ratio of biomass to nZVI was 100:1) was 100:3. The preparation methods reported in Chinese patent documents (CN117303492A, CN118598373A and CN118304857A) were selected to prepare samples with the same BC and nZVI ratio as in Example 1, and the effects of different materials on removing TC from water bodies were compared.

[0086] Comparative Example 2

[0087] The BC-nZVI composite material was prepared by a one-step pyrolysis method according to patent publication number CN117303492A, and the specific steps were as follows: 10 g BC prepared in comparative example 1 and 0.3 g nZVI were mixed evenly, and heat treated in a tube furnace at 750° C. During the heat treatment, N2 was introduced as a protective carrier gas at a flow rate of 0.5 L / min for 3 h.

[0088] Comparative Example 3

[0089] The BC-nZVI composite material was prepared by the pyrolysis-liquid phase reduction method in Patent Publication No. CN 118598373 A, and the specific steps are as follows: dissolve ferric chloride hexahydrate in deionized water to obtain a mixed solution; place pine wood chips in deionized water and stir them thoroughly, wash them repeatedly 5 times, and then dry the washed chips at 105°C for use; add 1.5g ferric chloride hexahydrate to 100ml deionized water to dissolve, then add 30g pine wood chips and stir them to obtain a suspension containing a solidified material; place the above suspension at room temperature for 24 hours; centrifuge the suspension to obtain a lower layer of solidified material; place the solidified material in a tubular furnace and heat treat it at 750°C. During the heat treatment, N2 was introduced as a protective carrier gas throughout the process, and the flow rate was maintained at 0.5L / min for 3h.

[0090] Comparative Example 4

[0091] The BC-nZVI composite material was prepared by the pyrolysis-liquid phase reduction method in Patent Publication No. CN118304857A, and the specific steps were as follows: 1.5 g of ferric chloride hexahydrate was dissolved in 100 ml of deionized water, and then 10 g of BC prepared in Comparative Example 1 was added and stirred to obtain a suspension containing a solidified material; the suspension was evaporated to dryness and placed in a tube furnace for heat treatment at 750 ° C. During the heat treatment, N2 was introduced as a protective carrier gas throughout the process, the flow rate was maintained at 0.5 L / min, and the time was 3 h.

[0092] Take 20mL of 20mg / LTC aqueous solution as simulated wastewater (pH 7.0, ionic strength 10mol / LNaCl), add 15mg of BC-nZVI composite material prepared by Example 1 and other three methods (the concentration of the corresponding material is 0.75g / L), oscillate at 200rpm in a constant temperature electric oscillator, and the reaction temperature is 25°C; sample is taken after 24h of equilibrium adsorption. The sample is centrifuged at 8000rpm for 30min, the supernatant is filtered through a 0.45μm membrane filter, and the concentration of TC in the supernatant is analyzed. The test results are shown in Table 2. It can be seen from the results that under the same experimental environment and the ratio of nZVI and BC, the preparation method of BC-nZVI material of the present invention has a higher removal effect on TC.

[0093] Table 2. Comparison of TC removal effects of BC-nZVI composites prepared by different methods

[0094]

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biochar-loaded nano-zero-valent iron composite material, characterized in that: The following steps are involved: The biomass material is crushed and evenly mixed with nano zero-valent iron particles to obtain a mixture, and the mixture is pyrolyzed to obtain a biochar-loaded nano zero-valent iron composite material.

2. The method for preparing the biochar-loaded nano-zero-valent iron composite material according to claim 1, characterized in that: The biomass material is forestry and / or agricultural waste.

3. The method for preparing the biochar-loaded nano-zero-valent iron composite material according to claim 2, characterized in that: The biomass material is pine wood chips.

4. The method for preparing the biochar-loaded nano-zero-valent iron composite material according to claim 3, characterized in that: The mass ratio of the biomass material to the nano zero-valent iron particles is 100:(0.5-5).

5. The method for preparing the biochar-loaded nano-zero-valent iron composite material according to claim 4, characterized in that: The particle size of the nano zero-valent iron particles is 5-500nm.

6. The method for preparing the biochar-loaded nano-zero-valent iron composite material according to claim 5, characterized in that: The pyrolysis temperature is 300-900° C., the pyrolysis time is 2-5 hours, and the pyrolysis process is carried out in an oxygen-free environment.

7. The biochar-loaded nano-zero-valent iron composite material prepared by the method according to any one of claims 1 to 6, characterized in that: The particle size of the biochar-loaded nano zero-valent iron composite material is no more than 150 μm.

8. The use of biochar loaded with nano zero-valent iron in wastewater treatment according to claim 7, characterized in that: The specific steps for removing tetracycline from wastewater are as follows: adding biochar-loaded nano-zero-valent iron composite materials to wastewater containing TC, adjusting the pH of the wastewater and subjecting it to constant temperature treatment, and then performing solid-liquid separation to remove solid materials from the system.

9. The use of biochar loaded with nano zero-valent iron in wastewater treatment according to claim 8, characterized in that: The concentration of the biochar-loaded nano zero-valent iron composite material in wastewater is 0.4-1.0 g / L.

10. The use of biochar loaded with nano zero-valent iron in wastewater treatment according to claim 8, characterized in that: The pH value is 7-8; the temperature of the constant temperature treatment is 20-30°C.